Synthesis and Antidepressant Activity of Some New 5-(1H-Indol-3-yl)-3-(substituted aryl)-4,5-dihydroisoxazoline Derivatives - Pravin O. Patil; Sanjay B. Bari (Journal of Chemistry)
The present study refers to the synthesis of new antidepressant candidates using the indole scaffold. In an attempt to identify potential lead antidepressant agents, a number of indole molecules, incorporating isoxazoline, were synthesized by microwave-assisted synthesis. The antidepressant activity of the synthesized compounds (3a–3n) was evaluated by forced swim test in mice and their locomotor activity was assessed using actophotometry. The present paper showed significant antidepressant activity for all compounds of the series and no significant change in locomotor activity of mice. Compounds 3d and 3j were found to be potent molecules of this series, when compared with the reference drugs imipramine and fluoxetine. It clearly demonstrated that replacement of aromatic core by appropriate heterocycles such as pyridine and pyrrole on the 5-(1H-Indol-3-yl)-3-(Phenyl)-4,5-dihydroisoxazoline (3a) would generate more potent derivatives. Thus, these compounds can serve as potential leads for further antidepressant studies.